Rola sieci innowacji w racjonalizacji cyklu innowacyjnego - Owczarek, Konstanty (Role of Innovation Networks in Innovation Cycle Rationalization, 2006)
The goal of the article is to discuss innovation networks. The terms innovation network and cluster were explained on top of describing reasons for delays in invention to innovation cycle. The author presents the role of innovation networks in solving the delay problem through sharing of risk research, development and marketing costs. Many case studies of use of innovation networks in solving innovation demand problems are included in the article.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 315-322